Unexpected variation in neuroanatomy among diverse nematode species - Ziduan eHan; Stephanie eBoas; Nathan eSchroeder; Nathan eSchroeder (Frontiers Media S.A., 2016)
Nematodes are considered excellent models for understanding fundamental aspects of neuron function. However, nematodes are less frequently used as models for examining the evolution of nervous systems. While the habitats and behaviors of nematodes are diverse, the neuroanatomy of nematodes is often considered highly conserved. A small number of nematode species greatly influences our understanding of nematode neurobiology. The free-living species Caenorhabditis elegans and, to a lesser extent, the mammalian gastrointestinal parasite Ascaris suum are, historically, the primary sources of knowledge regarding nematode neurobiology. Despite differences in size and habitat, C. elegans and Ascaris suum share a surprisingly similar neuroanatomy. Here, we examined species across several clades in the phylum Nematoda and show that there is a surprising degree of neuroanatomical variation both within and among nematode clades when compared to C. elegans and Ascaris. We found variation in the numbers of neurons in the ventral nerve cord and dye-filling pattern of sensory neurons. For example, we found that Pristionchus pacificus, a bacterial feeding species used for comparative developmental research, had 20% fewer ventral cord neurons compared to C. elegans. Steinernema carpocapse, an insect-parasitic nematode capable of jumping behavior, had 40% more ventral cord neurons than C. elegans. Interestingly, the non-jumping congeneric nematode, S. glaseri showed an identical number of ventral cord neurons as S. carpocapsae. There was also variability in the timing of neurodevelopment of the ventral cord with two of five species that hatch as second-stage juveniles showing delayed neurodevelopment. We also found unexpected variation in the dye-filling of sensory neurons among examined species. Again, sensory neuron dye-filling pattern did not strictly correlate with phylogeny. Our results demonstrate that variation in nematode neuroanatomy is more prevalent than previously assumed and recommend this diverse phylum for future evo-devo-neuro studies.